Multifunction bookshelves combine with table study and chair / Mohd Amar Md Aliudin, Norhafizah Rosman and Hanani Yuhaniz - Md Aliudin, Mohd Amar; Rosman, Norhafizah; Yuhaniz, Hanani (2014)
Limited space in houses and high priced furniture has become a problem people faced nowadays. Functions, design, space and material used to build up furniture is an important part in furniture. In this study, a multifunction product was designed to combat the problem of limited space. The multifunction book shelves combined with table study and chair made based on the demand of customer. The material used in this product is blockboard as the main material because of its good properties, more economical and lightweight. A set of questionnaires were distributed to 70 correspondents ranging people around from UiTM Jengka such as staffs, lecturers and students. Then the data were analysed using SPSS to get the results. The result shows that correspondent gave positive feedback regarding on the material used, simple design, easy to handle, storage book and stationeries, limited space uses, and multifunction. Overall, the multifunction book shelves combined with table study were accepted by all correspondents in accordance to age, gender and profession.